Pembelajaran Secara Daring atau Luring, Manakah yang Lebih Efektif untuk Mata Kuliah Pengantar Akuntansi? - Sofie Yunida Putri; Bayu Rama Laksono (BAJ: Behavioral Accounting Journal, 2022)
Along with the development of learning technology, it also developed. Initially, lectures could only be carried out face-to-face between lecturers and students. However, online lectures are now an alternative method when face-to-face lectures are impossible. This research is a comparative study that compares students’ level of understanding when lectures are held online and carried out offline to find out which is more effective when it is related to the level of understanding obtained by students. Student’s perspective is also one of the considerations in this study, students are asked to fill out a questionnaire regarding their level of understanding to be studied and compared with the stimulus in the form of a Pre-Test, Pre-Test Discussion, and Material Explanation to be studied by students' responses in the form of Post-Test scores before the lecture ends. Class leaders were also interviewed directly to find the right learning methods, especially as new students in the Introduction to Accounting course. The results of the student Pre-Test and Post-Test assessments show that grades when lectures are held offline, are better than grades when lectures are held online. 191 out of 193 students chose offline lectures as more suitable for their understanding, especially in the Introduction to Accounting course. The class president also mentioned connection problems during an interview as the main obstacle when lectures were held online.